Mesothelioma in Familial Mediterranean Fever With Colchicine Intolerance: A Case Report and Literature Review - Talerico, Rosa; Cardillo, Carmine; De Vito, Francesco; Schinzari, Francesca; Soldato, Manuel; Giustiniani, Maria Cristina; Verrecchia, Elena; Manna, Raffaele (Frontiers in Immunology, 2020)
A 65-year-old Italian physician affected by Familial Mediterranean Fever (FMF) was hospitalized due to progressive abdominal enlargement, which had begun two months before admission. Physical examination revealed ascites and bilateral leg oedema. The patient's past medical history revealed recurrent episodes of abdominal pain and fever from the age of two, but the clinical diagnosis was suspected at age 25, while genetic analysis obtained at age 50 showed homozygosity for the M694I mutation in the MEFV gene. Idiopathic asymptomatic leukopenia/lymphopenia was present since young age; the colchicine was prescribed but, although effective, it was not taken because it worsened the pre-existent leukopenia. Therefore, Canakinumab was prescribed as a second-line drug; but however, due to prescription issues, the patient was given Anakinra which resulted in worsening of leukopenia and subsequently septic fever. Abdominal CT scan showed ascitic fluid and extensive multiple peritoneal implants; peritoneal CT guided biopsy revealed an epithelial-type malignant mesothelioma. The systematic literature review indicates that in most FMF cases, recurrent peritoneal inflammation usually results in benign peritoneal fibrosis, or less commonly, encapsulating peritonitis and only few cases of FMF and peritoneal mesothelioma (MST) have been reported. In these FMF-MST case reports the colchicine intolerance or its erratic assumption is the common factor and the longstanding recurrent inflammation usual precedes the tumour development, whereas the constitutional leukopenia as in our case report could act as a predisposing factor. In conclusion, we suggest that in presence of colchicine intolerance (or resistance), the IL1 inhibition could suppress peritoneal inflammation and it seems highly advisable to prevent MST too.